Cost‐utility analysis of deep brain stimulation surgery plus best medical therapy versus best medical therapy in patients with Parkinson's: Economic evaluation alongside the PD SURG trial. Issue 8 (5th February 2016) - McIntosh, Emma; Gray, Alastair; Daniels, Jane; Gill, Steven; Ives, Natalie; Jenkinson, Crispin; Mitchell, Rosalind; Pall, Hardev; Patel, Smitaa; Quinn, Niall; Rick, Caroline; Wheatley, Keith; et al.
ABSTRACT: Introduction: Williams and colleagues reported that DBS surgery for patients with advanced PD improves motor function and quality of life compared to best medical therapy alone at 1 year, but with surgery‐related side effects in a minority. This article reports on the economic evaluation alongside this trial. Methods: Detailed resource use and quality of life over 12 months after randomization was obtained from the trial reported by Williams and colleagues. Outcomes were measured using the EQ‐5D and quality‐adjusted life years calculated. Results: Year 1 costs for surgery were significantly higher than in best medical therapy, at £19, 069 compared to £9, 813, a difference of £9, 256 (95% confidence interval [CI]: £7, 625, £10, 887). There was a small, significant gain in utility at 1 year but a statistically insignificant gain of 0.02 quality‐adjusted life years (95% CI: −0.015, 0.05) in the surgical arm. The incremental cost per quality‐adjusted life year of surgery at 1 year was £468, 528. Extrapolation reveals that after 5 years, this ratio is likely to reduce to £45, 180, but subsequently rise to £70, 537 at 10 years owing to the increased probability of battery replacements (and re‐replacements) beyond 5 years. Conclusion: In this patient group, DBS is not cost‐effective at 1 year. Extrapolation, however, reveals an increasing likelihood of cost‐effectiveness up to 5 years and reducing cost‐effectiveness between 5 and 10 years. These models are sensitive to assumptions about future costs and quality‐adjusted life years gained. © 2016 International Parkinson and Movement Disorder Society